Comparison of "high throughput" micromethods for determination of cytochrome P450 activities with classical methods using HPLC for product identification - Anzenbacherová, Eva; Veinlichová, Alena; Masek, Vlastimil; Anzenbacher, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
Enzyme activities of the CYP enzymes (CYP3A4, CYP2C9 and CYP2A6) were determined using classical substrates (testosterone, diclofenac and coumarin, respectively) as well as with luminogenic or fluorogenic substrates in micromethod arrangement. The luciferin-based luminogenic substrates for CYP3A4 and CYP2C9 as well as coumarin in micromethod for assay of CYP2A6 activity gave results well comparable with the classical methods with determination of reaction products by the HPLC.
Keywords: Cytochrome P-450 CYP3A; cytochrom P450 CYP2A6; diklofenak; testosteron; vysokoúčinná kapalinová chromatografie; lidé; cytochrom P-450 CYP3A; Coumarins; Mixed Function Oxygenases; Cytochrome P-450 CYP2A6; kumariny; Chromatography, High Pressure Liquid; Male; Diclofenac; Aryl Hydrocarbon Hydroxylases; systém (enzymů) cytochromů P-450; cytochrom P450 CYP2C9; Testosterone; mužské pohlaví; oxygenasy se smíšenou funkcí; Cytochrome P-450 CYP2C9; Cytochrome P-450 Enzyme System; aromatické hydroxylasy; Humans